Correlation study of Framingham risk score and vascular dementia: An observational study. Issue 50 (December 2017) - Li, Shan-Shan; Zheng, Jie; Mei, Bin; Wang, Han-Yao; Zheng, Miao; Zheng, Kai
Abstract : Abstract: Vascular dementia (VaD) is one of the most common forms of dementia, and second only to Alzheimer's disease. The purpose of this study was to evaluate the potential diagnostic value of Framingham risk score (FRS) in VaD by investigating the relationship among cardiovascular risks, FRS, and VaD. Data were collected from patients (n = 130) at Tongji Hospital in Wuhan, China. They were divided into 2 groups, including the control group (n = 70) and the VaD group (n = 60). Statistical methods including t- test, logistic regression model, multiple linear regression model, and receiver-operating characteristic (ROC) curve were adopted for the assessment. A significant difference (all P  < .05) was observed in systolic blood pressure (SBP), diastolic blood pressure (DBP), pulse pressure, total cholesterol (TC), homosysteine (HCY), glycosylated hemoglobin A1c (HbA1c), FRS, and cerebral white matter lesions (WMLs) between the 2 groups, even after adjusting for age (both P  < .05). Age [odds ratio (OR) = 1.20; P  = .002], FRS (OR = 1.55; P  = .006), and WMLs (OR = 10.17; P  = .011) were independent prognostic factors for VaD. The area under the ROC curve (AUC) of FRS for VaD diagnosis prediction was 0.830 (95% confidence interval, 95% CI: 0.730∼ 0.929). There was a significant difference in the AUC between WMLs and WMLs combined with FRS (0.788 (95% CI: 0.667 ∼ 0.880) versus 0.863 (95% CI: 0.754 ∼ 0.936, P  = .049). Age, HbA1c, and FRS were negatively correlated with the mini-mental state examination (MMSE) scores (all P  < .05) in the VaD group. Moreover, multiple stepwise linear regression analysis showed that the age and FRS were independent predictors of MMSE scores. FRS has a moderate predictive value for the VaD diagnosis, and also increases the risk of cognitive decline.